Vocational Career Center as the Bridge between Industry and Vocational High School Graduates - Indana, Luthfi; Soenarto, Soenarto (Jurnal Pendidikan Teknologi dan Kejuruan, 2019)
Preliminary study in Trenggalek city showed that there was a mismatch between the students’ skills learned at vocational high schools with their fields of work. It indicated that the role of vocational career center as a mediator between school and industry have not maximally yet. This study aimed to (1) describe how the vocational career center do its jobdesk, (2) categorize its performance, and (3) find the deficiency from the implementation of a career center in vocational high schools. The data analysis used a descriptive analysis from both quantitative and qualitative approaches. The result of study showed that the jobdesk of career center were collecting graduates databases, grouping the students who want to look for a job or study to higher education, and facilitating the students and world of work in the labour recruitment process. The performance of career center in Trenggalek Regency was good. From some predictors, those were job vacancy information, cooperation with world of work, alumni networking, data collection, communication between alumni, and alumni contribution, the career center’s aspect that need to be upgraded was the cooperation with the world of work.